Cyclopentadithiophene-cored non-fullerene acceptors for efficient polymer solar cells with superior stability. (1st November 2018) - Tang, Changquan; Chen, Shan-Ci; Tang, Yabing; Ma, Wei; Zheng, Qingdong
Graphical abstract: Two non-fullerene acceptorsSSBR andSSBRC cored with a simple cyclopentadithiophene are designed and synthesized facilely. The inverted devices based on PTB7-Th:SSBR afforded an initial PCE of 7.82%, and an increased PCE of 8.16% after 88 days storage. Furthermore, the best-performance device can retain about 98% of its initial PCE after more than 6 months storage demonstrating its superior stability. Highlights: Two non-fullerene acceptors cored with a simple cyclopentadithiophene are synthesized. The optimized devices based on two acceptors afford a high power conversion efficiency of 8.16%. The best-performance device can retain 98% of its initial PCE after more than 6 months storage. Abstract: The past few years has witnessed rapid progresses in the power conversion efficiencies (PCEs) of organic solar cells based on non-fullerene acceptors. However, most high-performance non-fullerene acceptors are synthesized by using complicated ring-fused aromatics which have relatively high synthetic cost. In this work, we report on the design and synthesis of two small molecule acceptors (SSBR andSSBRC ) by using a simple cyclopentadithiophene central core franked by 3-ethylrhodanine or 2-(1, 1-dicyanomethylene)-3-ethylrhodanine units with two benzothiadiazole bridges. The terminal electron-withdrawing groups have an important effect on physical, electronic and photovoltaic properties of the non-fullerene acceptors. Inverted polymer solar cells based on PTB7-Th:SSBRC showed an inferior PCE of 3.35%. In contrast, devices based on PTB7-Th:SSBR afforded an initial PCE of 7.82%, and an increased PCE of 8.16% after 88 days storage. Furthermore, the best performance device can retain about 98% of its initial PCE after more than 6 months storage demonstrating its superior stability.